Old Babylonian Letters. Part 1 - al-Zeebari, Akram (1964)
arabische Pagination; Published by the Directorate General of Antiquities, Republic of Iraq, Baghdad; 33 aB Briefe und 2 aB Rechtsurkunden; durch Beschlagnahme oder Schenkung in das Iraq Museum gelangt; Herkunft daher nicht sicher bestimmbar.